2013
DOI: 10.1093/infdis/jit348
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling in Childhood H1N1/09 Influenza Reveals Reduced Expression of Protein Synthesis Genes

Abstract: We compared the blood RNA transcriptome of children hospitalized with influenza A H1N1/09, respiratory syncytial virus (RSV) or bacterial infection, and healthy controls. Compared to controls, H1N1/09 patients showed increased expression of inflammatory pathway genes and reduced expression of adaptive immune pathway genes. This was validated on an independent cohort. The most significant function distinguishing H1N1/09 patients from controls was protein synthesis, with reduced gene expression. Reduced expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 15 publications
3
72
1
Order By: Relevance
“…The DRS method calculates a patient score by adding the total intensity of the up-regulated transcripts (relative to comparator group) and subtracting the total intensity of the down-regulated transcripts (relative to comparator group). The signatures identified in the discovery group were externally validated on previously published validation groups,13 additional patient groups with meningococcal disease and inflammatory diseases, and three pediatric and one adult published data sets (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DRS method calculates a patient score by adding the total intensity of the up-regulated transcripts (relative to comparator group) and subtracting the total intensity of the down-regulated transcripts (relative to comparator group). The signatures identified in the discovery group were externally validated on previously published validation groups,13 additional patient groups with meningococcal disease and inflammatory diseases, and three pediatric and one adult published data sets (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…1, 3). The validation groups comprised 130 UK and Spanish children previously recruited13 (IRIS validation – with 23 Definite Bacterial, 28 Definite Viral patients and 79 patients with indeterminate infection) and 72 additional validation children from the UK (25 children), Netherlands (30), and USA (17) – with 24 meningococcal infection, 30 juvenile idiopathic arthritis, and 18 patients with Henoch-Schönlein purpura) (Figs. 1 3).…”
Section: Resultsmentioning
confidence: 99%
“…Modules are groups of genes with similar biological functions. 13,14,2123 For these analyses, modular maps were derived independently for the training and test sets in both groups of patients (infants with and without bacterial infections) using the healthy control group as a reference. Modules related to interferon and inflammation genes are particularly relevant to identify differences in gene expression between infants with and without bacterial infections because these modules represent the major immune pathways activated in response to infections.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly interesting as recent findings have implicated a role of the H1N1 pandemic virus of 2009 as a trigger for narcolepsy development. 6 It has been suggested that the disruption of EIF pathways in childhood H1N1/09 influenza increases disease severity, 21 so polymorphisms in this locus could indirectly change immune responses to influenza and narcolepsy risk.…”
Section: Discussionmentioning
confidence: 99%